The Existence of the Roah Bale Beleq Tradition as a Reinforcement of the Spiritual and Social Aspects of the Community in Lombok - -, Lailatussakdiah; Widiastuti, Anik; -, Budiman; Ruhama, Ashfia; Susanti, Afifah Rizqi Aida (Institut Filsafat dan Teknologi Kreatif Ledalero, 2025)
This research aims to investigate the existence of the Roah Bale Beleq tradition in Wakan Village as a reinforcement of spiritual and social aspects. The research method employed is a descriptive-qualitative approach. Data collection techniques include interviews, observation, and documentation. Interviews were conducted with the head of the hamlet and traditional leaders. The results indicate that the Roah Bale Beleq tradition serves to strengthen spiritual aspects, such as ta'lim assemblies, dhikr, and communal prayers, as well as social aspects like cooperation and communal meals. These positive elements need to be preserved, making them among the reasons the tradition is still upheld today, despite changes such as reduced participant numbers and the discontinuation of traditional Lombok clothing, namely Lambung.Keywords: Existence of Tradition, Spiritual Aspect, Social Aspect